An under studied co-relation of diabetes and lung function - Das, Dona; Sridhar, R. V. (International Journal of Research in Medical Sciences, 2019)
The World Health Organization estimates that more than 180 million people worldwide have diabetes, and by 2030 it is expected that this number will have doubled. There is an alarming increase in the incidence and prevalence of diabetes mellitus (DM) in Asian Indians. Epidemiology of Diabetes in India. The prevalence of diabetes is rapidly rising all over the globe at an alarming rate . Over the past 30 years, the status of diabetes has changed from being considered as a mild disorder of the elderly to one of the major causes of morbidity and mortality affecting the youth and middle aged people. Pulmonary function test (PFT) is a complete evaluation of the respiratory system including patient history, physical examinations, and tests of pulmonary function. with insulin-dependent diabetes compared with age-matched control subjects, all lifelong non-smokers. Lung CO transfer capacity is significantly affected by the integrity of lung capillary endothelium and, therefore, the findings of Sandler et al. focused attention on pulmonary vascular changes. The concept of the lung as a target organ for diabetic microangiopathy received continuing attention. Reports of lung function tests in patients with diabetes over the next 15 years have focused largely on pulmonary microangiopathy with relatively few studies of pulmonary mechanical function which leads to a restrictive lung pattern. Diabetes and Lung Function Test : Some studies showed that all the pulmonary parameters, that is, FVC, FEV1, FEF25, FEF50, FEF75, FEF25–75, FEF0.2–1.2, and PEFR were significantly reduced except FEV1/FVC in patients of type 2 DM as compared with the healthy controls. It can be concluded from our narrative review that the Type II or Type I diabetes is definitely having decreased lung functions assessed by spirometry not only because of diabetic complications like pneumonia or other but also due to long term effect of diabetes may be because of micro-angiopathy or decreased elastic recoil capacity of lungs.